Head Injury Analysis of Vehicle Occupant in Frontal Crash Simulation: Case Study of ITBâs Formula SAE Race Car - Sandro Mihradi; Hari Golfianto; Andi Isra Mahyuddin; Tatacipta Dirgantara (Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
In the present study, frontal crash simulations were conducted to determine the effect of various car speeds against the Head Injury Criterion (HIC), a measure of the likelihood of head injury arising from impact. The frontal impact safety of ITB's formula SAE race car designed by students was evaluated as a case study. LS-DYNA®, an explicit finite element code for non-linear dynamic analysis was utilized in the analysis. To analyze head injury, a two-step simulation was conducted. In the first step, a full-frontal barrier test was simulated without incorporating a dummy inside the car. The output was the deceleration data of the car, which was used as input in the second step, a sled test simulation. In the sled test, only the cockpit and dummy were modeled. The effect of deceleration to the head of the dummy was then evaluated. The results show that HIC values at an impact speed of 7 m/s (25 km/h) to 11 m/s (40 km/h) were below the safe limit and still in the safe zone. However, the HIC values will exceed the safe limit when the speed of impact is the same as or greater than 12 m/s (43 km/h).